Facial rejuvenation with fat grafting: systematization and study of 151 consecutive cases - Eduardo Antonio Torres Furlani; Diego Bomfim Saboia (Revista Brasileira de Cirurgia Plástica)
Introduction: Considering that the loss of facial volume is a primary factor associated with aging, an increased demand for safe, long-lasting, and biocompatible filling materials has been observed. Thus, the use of fat grafting has gained considerable popularity. However, there are open questions about the safety, efficacy, and durability of fat grafting. Moreover, most studies have not presented the volumes injected in each region, making learning challenging for beginners in the area. In this study, the results of facial rejuvenation with fat grafting in 151 consecutive cases were analyzed. Methods: Fat was collected via manual suction, centrifuged at 448 g (2000 rpm/radius 10 cm) for 4 min, and injected with microcannulas that are 1-1.1 mm in size. The injection sites and corresponding injection volumes were identified. Results: The mean follow-up time was 289.29 days (minimum: 7 days, maximum: 1254 days, and standard deviation [SD]: 275.1), and the mean injection volume was 32 mL (range: 4-68 mL, SD: 14). Moreover, no complications were observed. Conclusion: Fat grafting is a safe, predictable, and effective procedure, and it can be used for facial rejuvenation in certain cases.